Phase management in single-crystalline vanadium dioxide beams - Run Shi (Nature Portfolio, 2021)
Control of the phases associated with the metal-insulator transition in VO2 underpins its applications as a phase change material. Here, the authors report phase management by means of oxide inhibitor-assisted growth and present high-performance VO2 actuators based on asymmetric phase transition routes.